(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Form of investment in infrastructure important factor to drive economic growth in any country, with the dwindling ability of governments to provide the necessary funds for such investments, emerged as a rising trend for private sector involvement in public projects and infrastructure, and one of these trends is the build-operate-transfer system (BOT), which commonly used in various developed and developing countries as one of the tools used in the implementation of these investments, as the private sector under this system design, finance, build and operate the project, and are re-administration of the state after a certain period under a contractual agreement between the parties of the contract. As this system provides major opportunities to create public projects and improved and developed and financed by the private sector with no load state budget further burdens as well as non-recourse borrowing for these projects from this perspective highlights the importance of this research evaluates the performance of this experience in Iraq and the extent of their success and achieving goals required.